The Structural Analysis of Adverbial of Manner in Ibibio (Eurasian Journal of Media and Communications, 2022)
This paper explores the structural analysis of adverbials of manner in Ibibio. In view of the fact that adverb or adverbial phrase of manner is an expression that supplies more information which qualifies the verb and answers the question ‘how’ and ‘in what way’ the action of the said verb is executed. It is pertinent to note that Ibibio is a growing language, spoken in Akwa Ibom State of Nigeria. The data used in this research were sourced from the Library, communication and interaction with the indigenous speakers of the speech form characterized as the Central Ibibio and recordings of special Ibibio programmes on radio and television, such programmes include Ntia-Ntia asakka, Akpan Mma Udobot and mbɅk mfin. The data so collected were carefully categorized based on my intuition as a native speaker of the speech form in focus. These were then classified and analyzed under the Eclectic Model consisting of a descriptive theory and the extended standard theory. The structural components of the analysis reveal that adverbials of manner are highly productive and can be systematically grouped based on their meanings, the sound associated with the word to a comparison process with appropriate scenarios. It is germane to point out that at the phrasal level the combination of adverbials of manner with either adjective or noun does not lead to any sematic ambiguity. Besides, like in some other African Languages, there are no adverbial affixes in Ibibio, as their inherent functions are subsumed by ideophones or reduplication. The existence of ideophones and onomatopoeic words in the lexicon indubitably confirms the claim that Ibibio is a creative and has the potential of rapid and consistent growth if empowered